The Importance of Metabolites in Modulating Insulin Sensitivity - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (Indonesian Biomedical Journal, 2022)
BACKGROUND: Metabolism impairment in obese condition usually initially triggered by inflammation and insulin signaling impairment. The involvement of metabolites, including lipids, amino acids, and ketone bodies, in altering insulin sensitivity has been revealed after massive data sets were provided by the studies regarding metabolomics and lipidomics.